2014
DOI: 10.5334/tohm.199
|View full text |Cite
|
Sign up to set email alerts
|

Tardive Syndromes are Rarely Reversible after Discontinuing Dopamine Receptor Blocking Agents: Experience from a University-based Movement Disorder Clinic

Abstract: Background: Several studies have examined reversibility of tardive syndromes (TS), primarily in psychotic patients who are maintained on dopamine receptor blocking drugs. The results have varied widely. However, few have assessed remission rates after discontinuing the offending agents. This study evaluated reversibility of TS in patients who permanently withdrew the causative agent(s). We also examined for any possible clinical predictors of reversibility. Methods: A retrospective cohort of 108 TS patients wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 15 publications
(25 reference statements)
0
45
0
Order By: Relevance
“…Considering the high incidence of clinically meaningful weight gain during SGA treatment, EPS partly lost their weight in clinical decision‐making. Nevertheless, TD remains a clinical problem in movement disorders clinics: SGA‐related tardive syndromes lately outnumbered FGA‐related TD cases in a movement disorders clinic, likely due to increasing on‐label, as well as off‐label use of SGAs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high incidence of clinically meaningful weight gain during SGA treatment, EPS partly lost their weight in clinical decision‐making. Nevertheless, TD remains a clinical problem in movement disorders clinics: SGA‐related tardive syndromes lately outnumbered FGA‐related TD cases in a movement disorders clinic, likely due to increasing on‐label, as well as off‐label use of SGAs.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous retrospective cohort study, we demonstrated that antipsychotic dose reductions resulted in significant increases in both all-cause and mental health-related hospitalizations, worsening the overall healthcare burden in schizophrenia patients [23]. However, there are no data examining the effect of dose reduction on symptoms of TD in mood disorders [20,24,25]. Even more important for clinical decision making, there is no evidence on the impact of antipsychotic dose reduction on the course of illness in patients with BD or MDD [14,26].…”
Section: Introductionmentioning
confidence: 95%
“…When side effects emerge during maintenance treatment with antipsychotics, management options include drug maintenance, discontinuation, switching, or dose reduction [5,6,12,[19][20][21][22][23]. For example, in patients with mood disorders in remission, maintenance treatment with antipsychotics may be unnecessary, and discontinuation may be reasonable to facilitate remission of TD or other side effects.…”
Section: Introductionmentioning
confidence: 99%
“…orofacial versus peripheral, especially dystonia) and durations of drug exposure and movement disorder. Recently, Zutshi et al (2014) reported very low rates of spontaneous reversibility: 2.8% over an average of 4.3 years. The paediatric literature strongly suggests that reversibility on antipsychotic cessation is the rule (Campbell 1988), whereas in working-age adults, it is much less predictable and in the elderly it is probably not likely (Gardos 1983).…”
Section: Course and Outcomementioning
confidence: 99%